(Invited) Transparent Top Gate Oxide TFT with ITO/Ag/ITO Low Resistance Electrode for the Application to the High Speed Operation Fingerprint Sensor Array in the Touch Panel. (18th August 2016) - Kim, Yujin; Jeon, Guk-Jin; Lee, Myung Keun; Lee, Seung Hee; Park, Sang-Hee Ko
Abstract : Oxide thin film transistor (TFT) and low-resistance electrode are necessary to manufacture transparent and high resolution fingerprint sensor for application to touch panel display. We adopted ITO/Ag/ITO triple layered stack as an electrode according to that inserting thin Ag layer between both sides of ITO layers definitely helps resistance decreases. Through simulation and optimization, we have chosen each thickness of three layers for optimal transmittance and sheet resistance, and developed dry etching conditions. Top gate structured IGZO TFT with triple layered S/D electrode showed outstanding electrical performance and is expected to be applied to transparent display panel.